Epidemiology of West Nile Disease in Europe and in the Mediterranean Basin from 2009 to 2013. (11th September 2014) - Di Sabatino, Daria; Bruno, Rossana; Sauro, Francesca; Danzetta, Maria Luisa; Cito, Francesca; Iannetti, Simona; Narcisi, Valeria; De Massis, Fabrizio; Calistri, Paolo
Abstract : West Nile virus (WNV) transmission has been confirmed in the last four years in Europe and in the Mediterranean Basin. An increasing concern towards West Nile disease (WND) has been observed due to the high number of human and animal cases reported in these areas confirming the importance of this zoonosis. A new epidemiological scenario is currently emerging: although new introductions of the virus from abroad are always possible, confirming the epidemiological role played by migratory birds, the infection endemisation in some European territories today is a reality supported by the constant reoccurrence of the same strains across years in the same geographical areas. Despite the WND reoccurrence in the Old World, the overwintering mechanisms are not well known, and the role of local resident birds or mosquitoes in this context is poorly understood. A recent new epidemiological scenario is the spread of lineage 2 strain across European and Mediterranean countries in regions where lineage 1 strain is still circulating creating favourable conditions for genetic reassortments and emergence of new strains. This paper summarizes the main epidemiological findings on WNV occurrence in Europe and in the Mediterranean Basin from 2009 to 2013, considering potential future spread patterns.